2020
DOI: 10.1002/hlca.202000184
|View full text |Cite
|
Sign up to set email alerts
|

Phenazine Radical Cations as Efficient Homogeneous and Heterogeneous Catalysts for the Cross‐Dehydrogenative Aza‐Henry Reaction

Abstract: The redox activity of molecular phenazine catalysts has been previously exploited for aerobic oxidative amine homo-and cross-coupling reactions. In this contribution, we have extended the reaction scope of this novel type of organocatalyst and used them in the cross-dehydrogenative aza-Henry coupling of isoquinolines with nitromethane under aerobic conditions. Additionally, we have designed and prepared a novel porous organic polymer by cross-linking of tetrakis(4-bromophenyl)silane and dihydrophenazine throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 112 publications
0
3
0
Order By: Relevance
“…Triarylaminium radical cations ( +• NAr 3 ) are exceptionally stable persistent radicals that are used in organic synthesis, materials science, and organometallic chemistry as mild yet relatively strong single electron oxidants "magic blue". 1) They are generally prepared from the corresponding neutral triarylamines (NAr 3 ) with the assistance of a silver-based oxidant 2) ; however, from an economic and environmental perspective, it would be desirable to avoid the use of a stoichiometric amount of such an expensive metal reagent, and thus, approaches to generate the radical cation more efficiently have recently been explored [3][4][5][6][7][8][9] (Chart 1a). Liu and Klussmann have reported that triarylamines can be oxidized in the presence of a stoichiometric amount of benzoyl peroxide and that the resulting triarylaminium radical cations successfully promote the difunctionalization of styrenes.…”
Section: Introductionmentioning
confidence: 99%
“…Triarylaminium radical cations ( +• NAr 3 ) are exceptionally stable persistent radicals that are used in organic synthesis, materials science, and organometallic chemistry as mild yet relatively strong single electron oxidants "magic blue". 1) They are generally prepared from the corresponding neutral triarylamines (NAr 3 ) with the assistance of a silver-based oxidant 2) ; however, from an economic and environmental perspective, it would be desirable to avoid the use of a stoichiometric amount of such an expensive metal reagent, and thus, approaches to generate the radical cation more efficiently have recently been explored [3][4][5][6][7][8][9] (Chart 1a). Liu and Klussmann have reported that triarylamines can be oxidized in the presence of a stoichiometric amount of benzoyl peroxide and that the resulting triarylaminium radical cations successfully promote the difunctionalization of styrenes.…”
Section: Introductionmentioning
confidence: 99%
“…17,24 Both the amines and the radical cations are also utilized as redox-catalysts in electrochemical 25,26 or photochemical reactions, 27,28 as well as in aerobic oxidations. 29,30 Despite this plethora of applications, we are not aware of amine-based redox catalysis in the activation of peroxides, which would open many opportunities for synthetic applications.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Aprile and co-workers reported the use of POSS-based materials as catalysts for the preparation of cyclic carbonates from CO 2 and epoxides, wherein the catalysts were successfully recovered and reused for four consecutive runs . In 2020, our group reported the efficient aza-Henry reaction , using phenazine-containing POSS-based polymers as a catalyst under aerobic conditions . POSS-based materials and composites have found also a relatively broad use in light-emitting applications, including photoelectronic, sensing, and imaging devices. Comparatively, the use of POSS-based POPs as a photocatalyst in organic synthesis remains scarce …”
Section: Introductionmentioning
confidence: 99%
“…40 In 2020, our group reported the efficient aza-Henry reaction 41,42 using phenazine-containing POSS-based polymers as a catalyst under aerobic conditions. 43 POSS-based materials and composites have found also a relatively broad use in light-emitting applications, including photoelectronic, sensing, and imaging devices. 44−47 Comparatively, the use of POSS-based POPs as a photocatalyst in organic synthesis remains scarce.…”
Section: ■ Introductionmentioning
confidence: 99%